2016
DOI: 10.1177/1558944716658747
|View full text |Cite
|
Sign up to set email alerts
|

The Scaphoid Staple: A Systematic Review

Abstract: For all indications, the scaphoid staple has a high union rate and a low complication rate. In the authors' experience, the procedure is fast, not technically challenging, and may be considered for primary fracture, delayed union, nonunion, and avascular necrosis of the scaphoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“… 21 22 SNUs fixed with SMS are stable and can therefore be compared with undisplaced fractures. 23 Hence, we decided to perform the immobilization for only 4 weeks after surgery to avoid immobilization overtreatment. In the literature, there is no unique way to define and characterize SNUs.…”
Section: Discussionmentioning
confidence: 99%
“… 21 22 SNUs fixed with SMS are stable and can therefore be compared with undisplaced fractures. 23 Hence, we decided to perform the immobilization for only 4 weeks after surgery to avoid immobilization overtreatment. In the literature, there is no unique way to define and characterize SNUs.…”
Section: Discussionmentioning
confidence: 99%
“…10 The pseudo-elastic properties of the staple allow for sustained compression and have been shown to be superior to traditional fixation methods in fractures of the scaphoid and midfoot. 7,11 Additionally, the lowprofile nature of the staple minimizes contact and subsequent irritation to the peroneal nerve, even with full knee extension. Compared to other salvage techniques for a lateralized fibular head tunnel, including use of suture anchors and redrilling, the described method using a compression staple is mechanically superior and results in a higher ultimate tensile strength compared to controls in response to uniaxial tension testing (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Dunn et al. (2017) recently published the first systematic review of scaphoid staples and reported union rates for acute waist fractures ( n = 77) to be 100% and return to work at 9.8 weeks.…”
Section: Operative Managementmentioning
confidence: 99%
“…In addition, Bain et al (2015) showed dorsal plating on the tension side of the fracture to be mechanically more sound; however, no clinical outcome studies comparing plate and screw fixation have been published yet. Dunn et al (2017) recently published the first systematic review of scaphoid staples and reported union rates for acute waist fractures (n = 77) to be 100% and return to work at 9.8 weeks. However, most studies on staples report their use in scaphoid nonunions, making generalizations for acute fractures difficult (Korkala and Antti-Poika, 1989;Korkala et al, 1992;Rocchi et al, 2005;Winkel and Schlageter, 2009).…”
Section: Operative Managementmentioning
confidence: 99%